Catalytic Production of Branched Small Alkanes from Biohydrocarbons. Issue 15 (11th June 2015) - Oya, Shin‐ichi; Kanno, Daisuke; Watanabe, Hideo; Tamura, Masazumi; Nakagawa, Yoshinao; Tomishige, Keiichi
Abstract Squalane, C30 algae‐derived branched hydrocarbon, was successfully converted to smaller hydrocarbons without skeletal isomerization and aromatization over ruthenium on ceria (Ru/CeO2). The internal CH2CH2 bonds located between branches are preferably dissociated to give branched alkanes with very simple distribution as compared with conventional methods using metal‐acid bifunctional catalysts.